MULTISENSORY METHOD IN IMPROVING CHILDREN'S READING ABILITY IN TAHFIDZ YATIM DHUAFA VILLAGE - Bakhdan Adika Trirona; Muhammad Alif Yahya; Nurul Fadilah Khoirunnisa; Heppy Savira Octavia; Syafaat Bayu Tirto; Tazkiya Izzatun Nisa Tazkiya (Taqrib : Journal of Islamic Studies and Education, 2023)
The problem in this study is about the low ability to read because there are limitations that are owned by children. This study aims to find out how the influence of the multisensory method in improving reading skills in children from Quran Village RTYD. The research method used in this research is quantitative research with experimental methods using Pre Experimental Design type two group pretest-posttest design. The population in this study were students of Quran Village RTYD and the samples in this study were children of class one Quran Village RTYD. The analysis technique uses independent sample t-test . The results showed that there was an effect of the multisensory method on children's reading ability, this could be seen in the control group, there was no significant difference in score (p > 0.05), then an independent sample t-test was performed and the results showed that the difference in pretest scores between the experimental and control groups was not significant (P < 0.05).